CONSUMERISM DAN PERLINDUNGAN KONSUMEN - Fatchurrohman Fatchurrohman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2006)
Consumerism has become an important issue in consumer behavior. Consumerism known as asocial movement to strengthen the rights and powers of buyers in relation to sellers. There are threeinstitutions which have major role in consumerism, they are consumer organization, government andcompany. Consumer organization gives information and advocacy to consumer. Government have aresponsible in the regulation and legislation of consumer rights. Finally, company have their own role toenforce self regulation about consumerism. Consumerism has developed into green consumerism. It means that consumer emphazises theirattention in the environment issue. Consumerism has a major implication to the marketingmanagement in a company. One of them is more attention in producing safe product by the company.Developed country implements consumerism in day to day company strategies while developing countriesconsider this as a new emerging issue.